Confinement of Candida Antarctica Lipase B in a Multifunctional Cyclodextrin-Derived Silicified Hydrogel and Its Application as Enzymatic Nanoreactor - Decarpigny, Cédric; Bleta, Rudina; Ponchel, Anne; Monflier, Eric (ACS Applied Bio Materials, 2019)
International audience Supramolecular hydrogels with a three-dimensional cross-linked macromolecular network have attracted growing scientific interest in recent years because of their ability to incorporate high loadings of bioactive molecules such as drugs, proteins, antibodies, peptides, and genes. Herein, we report a versatile approach for the confinement of Candida antarctica lipase B (CALB) within a silica-strengthened cyclodextrin-derived supramolecular hydrogel and demonstrate its potential application in the selective oxidation of 2,5-diformylfuran (DFF) to 2,5-furandicarboxylic acid (FDCA) under mild conditions. The enzymatic nanoreactor was deeply characterized using thermogravimetric analysis, Fourier transform infrared spectroscopy, N 2 -adsorption, dynamic light scattering, UV–visible spectroscopy, transmission electron microscopy, scanning electron microscopy, and confocal laser scanning microscopy, while the reaction products were established on the basis of 1H nuclear magnetic resonance spectroscopy combined with high-performance liquid chromatography. Our results revealed that while CALB immobilized in conventional sol–gel silica yielded exclusively 5-formylfuran-2-carboxylic acid (FFCA), confinement of the enzyme in the silicified hydrogel imparted a 5-fold increase in DFF conversion and afforded 67% FDCA yield in 7 h and almost quantitative yields in less than 24 h. The hierarchically interconnected pore structure of the host matrix was found to provide a readily accessible diffusion path for reactants and products, while its flexible hydrophilic–hydrophobic interface was extremely beneficial for the interfacial activation of the immobilized lipase.